THE IMPACT OF ENVIRONMENTAL PERFORMANCE AS REALIZATION OF ENVIRONMENTAL REGULATION ON FINANCIAL PERFORMANCE - Prayanthi, Ika; Mandagi, Deske (The International Journal of Accounting and Business Society, 2015)
The purpose of this study is to assert the impact of environmental performance as realization of environtmental regulation on financial performance for the span of one to three years (2010-2013) after the publication of environmental performance ratings. Environmental performance was measured by the ratings given by PROPER program, and financial performance was measured based on ROA and ROE. This study also examined if there is significant difference on financial performance among the group of companies on each rating. The research finding shows that there was no significant impact of environmental performance on financial performance on the first year announcement of the financial ratings, however there was a significant impact on the second and third year. Different tests using ONE WAY ANOVA indicated that there was significant difference on financial performance of companies in different rating, in each year. The result suggested that companies with green rating had the highest financial performance followed by gold rating.Keywords: environmental performance, return on asset, return on equity.